Remaja Putus Sekolah dalam Perspektif Gender di Desa Baktirasa Kecamatan Sragi Kabupaten Lampung Selatan - Rizaludin Rizaludin; Muhammad Basri; Suparman Arif (FKIP UNIVERSITAS LAMPUNG, 2019)
The purpose of this study is to determine factors causing teenagers dropped out school from the gender perspective in Baktirasa Village, Sragi District, South Lampung Regency. The method of the study was done using Descriptive Qualitative Method. The results of the study on teenagers dropping out school was caused by several factors including economic factor, social factor and cultural factors. There was a cultural perspective in the community of Baktirasa Village that girls do not need to go for higher education - it is enough for them to be able to read and write because they will eventually become housewives whose activities are mainly in the kitchen, wells and mattresses. From the gender perspective according to Liberalism Feminism gender theory, such condition is a deviant matter in gender because it demeans the position of women for being school dropouts since the position of men and women should be uqual in any matter.Tujuan Penelitian mengetahui faktor- faktor penyebab remaja putus sekolah dalam persfektip gender di Desa Baktirasa Kecamatan Sragi Kabupaten Lampung Selatan. Metode Penelitian menggunakan Metode Deskriptif Kualitatif Hasil Penelitian Remaja Putus sekolah disebabkan oleh beberapa faktor diantaranya faktor Ekonomi, faktor Sosial dan faktor Budaya, masyarakat di Desa Baktirasa masih mempunyai sudut pandang dan budaya yang mana anak perempuan tidak perlu sekolah tinggi- tinggi cukup bisa membaca dan menulis saja dikarenakan mereka nantinya akan menjadi ibu rumah tangga yang kegiatannya hanya di dapur, sumur dan di kasur. Hal tersebut dalam sudut pandang gender menurut Teorigender Liberalisme Feminisme merupakan suatu hal yang menyimpang dalam gender karena merendahkan kedudukan perempuan yang putus sekolah yang mana selayaknya kedudukan laki- laki dan perempuan harus sama dalam hal apa pun menurut teori gender tersebut.Kata kunci: gender, putus sekolah, remaja